A Mechano-Feedback Loop Orchestrated by SUN1/2 Governs Cellular Mechanoadaptation via Lamina-Associated Domain Remodeling - Xie, Yafan; Zuo, Zhaoyan; Zhao, Yanjing; Guo, Liping; Xu, Wei; Qiu, Juhui; Wang, Guixue; Peng, Qin (浪淘沙预印本平台, 2025)
SUN1/2, core components of the linker of nucleoskeleton and cytoskeleton (LINC) complex, transmit extracellular mechanical forces to nuclear lamina and chromatin. However, their role in regulating peripheral chromatin in mechanosensing and mechanoadaptation remains unclear. Using CRISPR/Cas9-mediated knockout of Sun1 or Sun2 in myoblasts, we identified a SUN1/2-dependent mechano-feedback loop. SUN1/2 depletion downregulates genes for cell adhesion (e.g., integrin a4) and mechanotransduction (e.g., talin, RhoA). The primary mechanism involves redistribution of heterochromatin from nuclear periphery to the nucleoplasm and remodeling of lamina-associated domains (LADs), as an adaptive response to the loss of SUN proteins. Furthermore, lamin A/C acts as a key downstream effector, consistently modulating adhesion-related gene expression through the remodeling of LADs. Functionally, knockout of either Sun1/2 or Lmna aggravates differentiation defects in C2C12 myoblasts and abolishes adaptive responses to mechanical cues. This study provides proof-of-concept that nuclear mechanotransduction proteins can modulate cellular mechanoadaptation via a mechano-feedback loop, which coordinates LADs reorganization with the expression of upstream mechanotransduction genes.